Etnična sestava prebivalstva in medetnični odnosi v Velenju - Zupančič, Jernej (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2005)
Velenje is a typical example of a Slovene industrial coal mining town with distinctly mixed ethnic structure, caused mostly by rapid population growth and immigration. The rapid expansion of coal mining and industry in the 1960s and 1970s kept providing new jobs that were taken by immigrants from regions of the former federal state - Bosnia, Herzegovina, Croatia, Macedonia and Serbia. The ethnic structure of population was getting more and more diverse. In the beginning workers in coal mining were mostly men, so there were many marriages between immigrants and locals already in the first generation.This caused better integration of immigrants into the new surroundings. The vicinity and intensity of communication in the apartment bloc districts calledfor coexistence between immigrants belonging to different ethnic groups.Moreover, they were of relatively equal social status, as coal mining and basic industry were strongly favoured in the ideology of socialist system.The latter also supported the ideology of interethnic coexistence, expressed in the slogan Ćunity and brotherhoodĆ. Yet this coexistence was not without frictions. After Sloveniaćs gaining independence, conflicts between groups increased, mostly due to ethnic polarization in immigrantsć original settings, and less so between Slovenes and members of other ethnic groups, although this phenomenon is also noticeable. Manifestations of cultural differences and differences, arising from religion, are also becoming more frequent. The article presents the present ethnic structure of the population of Velenje, and the quality of interethnic relations between individual ethnicgroups, based on field research project, carried out in 2004.
Keywords: etnična struktura; medetnični odnosi; prebivalstvo; Velenje; Slovenia; Slovenija; raziskave